ANALISIS AKUNTANSI ZAKAT BERDASARKAN PSAK NO. 109 PADA BADAN AMIL ZAKAT NASIONAL (BAZNAS) SUMATERA UTARA - Pandapotan Ritonga (KITABAH: Jurnal Akuntansi dan Keuangan Syariah, 2017)
The purpose of this study is determine whether the accounting treatment of zakat in BAZNAS North Sumatra accordance with PSAK No. 109. This research is conducted to examine the financial statements prepared BAZNAS North Sumatra and to determine the application zakah, sadaqah and infaq accordance with PSAK No. 109 on Accounting for Zakat. The method used is descriptive approach and this type of data is qualitative. the results of this research concluded that BAZNAS North Sumatra have not fully implemented use PSAK No.109. in presenting the financial statements. because in PSAK No. 109, zakah accounting aims to regulate the recognition, measurement, presentation and disclosure of transactions zakah, infaq/ Sadaqah.